Joseph Jurt: «Mi comparatismo es tanto interdisciplinar como interliterario» - Martí Monterde, Antoni (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Interview to Joseph Jurt
Keywords: Joseph Jurt; interview